2022
DOI: 10.1039/d1cp05186e
|View full text |Cite
|
Sign up to set email alerts
|

T- and pH-dependent OH radical reaction kinetics with glycine, alanine, serine, and threonine in the aqueous phase

Abstract: Glycine, alanine, serine, and threonine are essential amino acids originating from biological activities. These substances can be emitted into the atmosphere directly. Within the present study, the aqueous phase reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Scheme illustrates the mechanism of the OH radical-induced H-atom abstraction reaction with tartaric acid and the possible electron transfer, with H-atom abstraction being the main reaction pathway. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme illustrates the mechanism of the OH radical-induced H-atom abstraction reaction with tartaric acid and the possible electron transfer, with H-atom abstraction being the main reaction pathway. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Scheme 1 illustrates the mechanism of the OH radical-induced H-atom abstraction reaction with tartaric acid and the possible electron transfer, with H-atom abstraction being the main reaction pathway. 11,29,32,33 An alkyl radical is formed, which immediately reacts with O 2 to form an α-hydroxy peroxyl radical. 32,34 In this case, the αhydroxy peroxyl radical decomposes into an HO 2 radical and the corresponding carbonyl compound 2-hydroxy-3-oxosuccinic acid.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors, such as free radicals, and ultraviolet radiation, may oxidize the amino acids in different environments. [6][7][8][9][10][11][12][13][14] Stadtman et al 6 investigated the oxidation of amino acids by hydroxyl radical (HO  ) produced by the Fenton reagent, i.e., -Fe(II)+H 2 O 2 system. The obtained products were NH 4 + , α-ketoacids, CO 2 , oximes, and aldehydes or carboxylic acids containing one less carbon atom.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the reaction rates varied from 5×10 5 to 6×10 7 M -1 s -1 , with the decreasing order being the following: His > Trp > Tyr > Met. Wen et al 8 experimentally and theoretically performed the influences of temperature and pH on the oxidations of glycine (Gly), alanine (Ala), serine (Ser), and threonine (Thr) in the aqueous phase by HO • radical. The authors observed that the oxidation rate constants of these amino acids increased from 1.3 to 3 times when the temperature grew from 278 to 318K.…”
Section: Introductionmentioning
confidence: 99%